Teachers’ concepts of a ‘no penalty zone’. Drama-based learning for inclusive and co-designed classrooms - Colverd, Susan; Jagiełło-Rusiłowski, Adam (Adult Education Discourses, 2022)
The pandemic related restrictions for schooling became a momentum for redefining teachers’ competences to engage students in designing learning situations as equals. In the COVID-19 context the educators trained in drama identified it as a key professional resource for sharing power and inclusion of students’ diversity. The aim of the study is to explore how teachers understand ‘no penalty zone’ in their critical incident protocols and what training support they need for professional development. The construct of ‘no penalty zone’ is taken from the theory and practice of drama by Dorothy Heathcote. The rationale for combining reflective teachers’ practices with drama comes from the theory of liberating pedagogy of Paulo Freire. Previous research on drama as a democratising tool for co-designed learning is presented. The study analyses the teacher’s concepts in juxtaposition to the incidents they chose as vicarious experiences. The results reveal personal meanings of mutual empowerment that teachers see in learning through ‘no penalty zone’, unique paths they have taken from totally transmissive and often high-pressured classrooms to power sharing leading to inclusivity and creativity in their classrooms. They also show the further need for drama framing skill-oriented teacher training.